(untitled) (Quinto Sol, 2012)
This article analyzes the funerals organized by the Argentine National State from 1906 to 1914. These funerals were considered as rites of passage and as public feasts through which the regime honored their great men as well as their own merits. This paper deals with the peculiar characteristics of each funeral, although it lays emphasis on their common features and particularly on grasping the similar political message given by the State. It looks at the pedagogic role that the government elites attributed to these funerals for the sake of order, civic mindedness and republican austerity. State funerals also made way for public and sometimes private work related to memory and posthumous celebration. The last section of the article speculates about the possible reasons why the bodies of these “great men”, acclaimed by the State and by a significant part of the population at the time of their death, do not enjoy cult status or are objects of deliberate manipulations neither in the 20th century nor at present.